Attorney general: role and powers - Ali Mohamed, Ashgar Ali; Mallow, Muzaffar Shah (CLJ Publication, 2020)
The Attorney General is the principal legal adviser to the Government of Malaysia on matters of law and legal opinion. He is appointed by the Yang di-Pertuan Agong (YDPA) on the advice of the Prime Minister from among a person who is qualified to be a judge of the Federal Court.2 Article 123 of the Federal Constitution provides that a person is qualified to be appointed as a Federal Court judge if for the ten years preceding his appointment, he has been an advocate, a member of the judicial and legal service of the Federation or of the legal service of a state, or sometimes one and sometimes another. The Attorney General shall hold office during the pleasure of the Yang di-Pertuan Agong and shall not be removed from office except on the like grounds and in the like manner as a judge of the Federal Cour